Effect of anchorage number and CFRP strips length on behavior of strengthened glulam timber beam for flexural loading - İşleyen, Ümmü Karagöz; Ghoroubi, Rahim; Mercimek, Ömer; Anıl, Özgür; Togay, Abdullah; Erdem, R Tuğrul (SAGE Publications, 2021)
Laminated wooden beams are more preferred in the production of wooden structures than solid timber beams because they have a higher load-carrying capacity and allow larger openings to be used in the structure. The widespread use of wooden structures and the increasing size of the structures have revealed the need for strengthened laminated wooden beams and increase their ultimate load capacity. It has become necessary to develop reinforcement details to increase the ultimate load capacity of laminated wooden beams in wooden railroads or highway bridge beams, where the traffic load increases, especially in large wooden structures, in cases where large openings must be passed. Within the horizon of the study, the behavior and performance of three-layer glulam wooden beams strengthened with anchorage and non-anchorage CFRP strips with different bonding length under flexural loading were investigated experimentally. The three-point bending test was applied to glulam timber beam test specimens produced by laminating yellow pine wood material using the polyurethane adhesive. General load-displacement behaviors, ultimate load capacity, initial stiffness, displacement ductility ratios, and energy dissipation capacities were obtained. The increase in the bonding length of the CFRP strips used for strengthening in the glulam timber beam specimens and the use of CFRP fan type anchors at the strip ends increased the ultimate load capacity and initial stiffness values of the wooden beams, as well as the displacement ductility ratios and energy dissipation capacity values.